Geomorphology of subglacial volcanoes in the Azas Plateau, the Tuva Republic, Russia. - KOMATSU, Goro; S. G. ARZHANNIKOV; A. V. ARZHANNIKOVA; K. ERSHOV (Geomorphology, 2007)
The Azas Plateau volcanic field is located in the Tuva Republic of the Russian Federation. The compositions of the Azas Plateau volcanics include low-viscosity trachybasalt and basanite. Volcanic edifices of Middle-Late Pleistocene age are widely distributed in the southeastern part of the volcanic field. There are subglacial volcanoes among the volcanic edifices, and their formation coincided with extensive ancient glaciations in the region. The dominant subglacial volcanoes in the area are tuyas. The general shapes of the tuyas (flat-tops with steep sides) are due to eruptions into meltwater lakes and confinement of ice walls, and effusive subaerial eruptions of basaltic lavas. There are also non-flat-topped subglacial volcanoes and at least one subaerial volcanic edifice in the area. Degradation appears to have modified the primary shapes of the tuya edifices, and such processes seem to include failures of over-steepened slopes, gully formation due to stream runoff and debris flows, cirque/valley glaciation, and modification by rock glaciers. The estimated thicknesses of the ice sheets covering the subglacial volcanoes during their eruptions range 300–600 m on average.